SURAT DAKWAAN CAMPURANTINDAK PIDANA PENCUCIAN UANG BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA (STUDI PUTUSANNO..488/PID.B/2021/PN.JKT.BRT): Indictment Letter of Combined Criminal Acts of Money Laundering Based On The Criminal Procedure Code (Study of Decision No. 488/Pid.B/2021/Pn.Jkt.Brt) - Nurjanah; Widjajanti, Ermania (Faculty of Law, Universitas Trisakti, 2024)
Drafting a charge is the most important aspect of criminal procedure, as the trial commences based on this document. Therefore, the Public Prosecutor (JPU) must carefully prepare the charge before submitting it to the district court. There are five forms of charges, namely single, alternative, subsidiary, cumulative, and combined charges. In this case, the defendant, Calvin Seidiono, was charged with a combined charge (alternative, cumulative, subsidiary) and was found guilty of money laundering. The problems raised in this journal are: 1) Is the combined charge for money laundering against the defendant appropriate? 2) What are the legal consequences if one of the criminal offences alleged by the JPU in the combined charge is not proven? To answer the research questions, the author conducted a normative study that was descriptively analyzed using secondary data. The data processing was qualitative and the conclusions were drawn using deductive logic. This study found that: 1) The prosecutor did not take the appropriate action in drafting the charge. This is because all elements must be proven when choosing a combined charge (alternative, cumulative, subsidiary). all elements must be proven. However, in the case examined in this study, only one crime was proven, so the form of the charge was inappropriate. 2) Regarding the legal consequences if one of the elements of the combined charge is not proven, the judge should have acquitted thedefendant.